Análise das práticas da gestão da qualidade em fabricantes de equipamentos para a indústria de alimentos do estado de São Paulo - Mastrantonio, Sabrina Di Salvo (Universidade Federal de São Carlos, 2009)
The capital good supplier for the food industry have encountered a new reality in the market, with the increase of requirements in the product quality improvement by, as well the adjustment of the equipments to the regulatory requirement of food security. Towards this, the companies seek to implant some practices, aiming the product quality assurance and the process improvement, which can be gotten by the Quality Management System (QMS) structure, in the company scope and in the whole production chain. The strong dependence of technology innovation of the food industry, not only to the raw material industry, but also to the capital good supplier, emphasize the importance that this segment exerts over the food production chain, spreading new technologies and new quality patterns. This Master s paper analyze the Quality Management practices in a sampling of machinery and equipment manufacturers for the food industry, located in the state of São Paulo, as well the difficulties found in this Management and propose improvement suggestions. A survey was conducted, by visit and in loco interviews in 35 companies, of different sizes, acting segment and geography localization in the state of São Paulo. The data were analyzed with the purpose of characterize the companies, test possible correlations among the study variables and group the companies with similar characteristics in clusters. The correlation analysis showed dependence among some variables, as the level of formalization of the procedures and the existence of a Quality Management System. The cluster analyses generates 3 groups of companies, which can be distinguished, mainly, by the degree of the procedure formalization, existence of a Quality Management System and the company size. It was observed that the companies of this sector are diversified in their line of business and that they supply equipments not only to the food industry, but also to all those industries which need equipments made of stainless steel. It could be seen that, although the product quality is an overall demand in this segment, the existence of a QMS is not, which somewhat, contradict the initial expectative of this paper and publications in this area. However, the companies that supply equipments to other sectors, normally more demanding, as the petrochemical, or which visualize the benefits in the quality and productivity improvements reached with the QSM adoption, have already anticipated possible future demands of their clients, implanting and searching for the system certification.
Keywords: Gestão da qualidade; Alimentos - indústria; Máquinas e equipamentos; Survey; Quality management; Food industry; Equipment for food industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO